Multi-robotic system path planning based on RTM - Ke Wang; Songmin Jia; Yuchen Li; Xiuzhi Li (2012 Proceedings of SICE Annual Conference (SICE), 2012)
Multi-robotic system is widely used in exploring in large-scale unknown environment and performing the complex tasks. This paper presents exploration mode and goal oriented mode of path planning for multi-robotic system using RTM as communication platform. We use the Player Project works as simulation platform to realize topological map for multi-robotic system and use SP 2 ATM algorithm for path planning. In order to improve the effectiveness of the path planning, ICP algorithm is used for robot's localization. This paper presents the architecture of the proposed method and gives some experiments to verify the effectiveness.